Effectiveness of social assistance distribution to the community in the Otomona Village, Mimika District Central Papua Province - Faridah, Faridah; Marlissa, Elsyan R.; Urip, Transna Putra (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to evaluate the effectiveness of social assistance distribution in Otomona Village, Mimika Regency, focusing on value accuracy, target accuracy, and timeliness. The research seeks to identify strengths and weaknesses of the program and provide recommendations for improvement. Research/methodology: The study employed a descriptive qualitative approach using purposive sampling of 30 respondents who were recipients of Direct Cash Assistance (BLT). Data were collected through structured interviews, participatory observation, and documentation of official records. The analysis emphasized transparency, distribution mechanisms, and recipients’ perspectives. Results: Findings reveal that value accuracy has been achieved, as all respondents consistently received Rp 200,000 per month without deductions or administrative fees. However, challenges remain in targeting and timeliness. About 80% of respondents had incomes below the regional minimum wage, confirming appropriate targeting, yet variations in housing conditions highlight inconsistencies in eligibility criteria. Additionally, 44% of respondents reported delays in receiving assistance, showing weaknesses in timeliness. Conclusions: The distribution of social assistance in Otomona Village has been effective in terms of value accuracy but requires improvement in targeting and timeliness to ensure fairness and consistency. Enhancing coordination, updating beneficiary data, and leveraging technology are key strategies to increase program effectiveness. Limitations: The study was limited to 30 respondents in one village, which restricts generalizability. Broader and comparative studies are needed to capture diverse regional contexts. Contribution: This research provides empirical evidence on the performance of social assistance programs at the village level and offers practical recommendations to strengthen policy implementation and improve social welfare outcomes.